Hydrochar enhances growth of poplar for bioenergy while marginally contributing to direct soil carbon sequestration. Issue 11 (2nd June 2017) - Baronti, Silvia; Alberti, Giorgio; Camin, Federica; Criscuoli, Irene; Genesio, Lorenzo; Mass, Robert; Vaccari, Francesco P.; Ziller, Luca; Miglietta, Franco
Abstract: Hydrothermal carbonization (HTC) has been proposed as an alternative method to pyrolysis for producing C‐rich amendments for soil C sequestration. However, the use of hydrochar (HC) as soil amendment is still controversial due to the limited information on the potential benefits and trade‐offs that may follow its application into soil. This study investigated the effects of HC starting from maize silage on plant growth in a 2‐year controlled experiment on poplar for bioenergy and evaluated HC stability in soil by periodic soil respiration and isotopic ( δ 13 C) measurements. HC application caused a substantial and significant increase in plant biomass after one and two years after planting, and no evident signs of plant diseases were evident. Isotopic analysis on soil and CO2 efflux showed that slightly less than half of the C applied was re‐emitted as CO2 within 12 months. On the contrary, considering that the difference in the amount of N fixed in wood biomass in treated and not‐treated poplars was 16.6 ± 4.8 g N m −2 and that the soil N stocks after one year since application did not significantly change, we estimated that approximately 85% of the N applied with HC could have been potentially lost as leachate or volatilized into the atmosphere as N2 O, in response to nitrification/denitrification processes in the soil. Thus, the permanence, additionality and leakage of C sequestration strategy using HC are deeply discussed.